Assessment of a portable lactate meter for field use in the white rhinoceros (Ceratotherium simum) - Georgina C. Cole; Adrian S.W. Tordiffe; Gerhard Steenkamp (Onderstepoort Journal of Veterinary Research, 2017)
Blood lactate is a predictor of mortality in critically ill humans and animals. Handheld lactate meters have the potential to be used in the field to evaluate the condition of severely injured rhinoceroses but have not been compared with laboratory-based methods. Agreement between a handheld lactate meter and a laboratory method was assessed, as was the stability of rhino blood lactate in the anticoagulant sodium fluoride/potassium oxalate (fluoride/oxalate). Blood samples were obtained from 53 white rhinos that had been immobilised for management reasons. Lactate was measured by means of a handheld meter using whole blood in heparin (WBHEP), whole blood in fluoride/oxalate (WBFO) and fluoride/oxalate plasma (PFO). Results were recorded in both blood (BL) and plasma (PL) modes and compared to an established laboratory method for measuring plasma lactate. To assess the stability of lactate over time, blood lactate in fluoride/oxalate was measured on the handheld meter at intervals for up to 91 h. Agreement was best using WBFO in PL mode, with small bias (-0.16), tight 95% limits of agreement (LOA) (-1.46, 1.14) and a Pc (95% CI) of 0.97 (0.92, 0.99). The agreement was improved for all sample types when using the PL mode compared to the blood lactate (BL) mode. Blood lactate was stable in fluoride/oxalate for 91 h, with a mean change from baseline of 0.15 (-0.178, 0.478) mmol/L (mean, 95% CI). The handheld meter was found to be suitable for field use in white rhinos but provided more reliable results with the device in PL mode. Furthermore, rhino blood lactate was found to be stable in fluoride/oxalate for as long as 3 days.